Natural Family Planning: Nursing Perspectives and Patient-Centered Care - Alenazi, GHADAh Kalaf; Ashwag Ahmed Ali Montaser,; Emadah Ahmed Ali Muntasir,; Muneera Bader Nasser Alomeerah,; Khulud Abdulaziz Abdulaal,; Awatef Thamer Alharbi,; Sohair Yahya Awam,; Abeer Ali Almatrafi,; Safia Ibrahim Al-Fifi,; Sara Manaa Al-Kedessi,; Dina Abdou Rdouh, (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Natural Family Planning (NFP) encompasses fertility awareness–based methods that enable individuals and couples to achieve or avoid pregnancy by identifying fertile and infertile periods of the menstrual cycle. Although global utilization remains low, NFP offers a non-pharmacological, reversible option aligned with personal, cultural, and religious values while avoiding adverse effects associated with hormonal or device-based contraception. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This article aims to examine the principles, effectiveness, methods, and clinical significance of natural family planning, with particular emphasis on nursing roles, patient-centered care, and interprofessional collaboration. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> A narrative review approach was used to synthesize existing evidence and clinical guidelines on NFP. The article reviews physiological foundations of fertility awareness, describes major NFP methods, and discusses nursing, allied health, and interprofessional interventions and monitoring strategies. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> NFP effectiveness varies widely depending on the method used, quality of education, and user adherence. Fertility awareness–based methods such as the Standard Days, Billings, Symptothermal, Marquette, and Lactational Amenorrhea Methods demonstrate lower failure rates with correct use compared to typical use. Nurses play a central role in education, counseling, monitoring menstrual regularity, and supporting adherence. Interprofessional collaboration enhances continuity, accuracy of instruction, and patient confidence. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> NFP represents a patient-centered and evidence-informed family planning option that requires structured education, ongoing monitoring, and collaborative care to optimize outcomes and support reproductive autonomy.